Effect of Antioxidant Supplementation in Cancer Patients on Radiotherapy - RY, Patil; HN, More (Indian Journal of Pharmacy Practice)
Introduction: Cancer and its treatment by radiotherapy are believed to be associated with oxidative stress. A study was carried out to assess the oxidant and antioxidant status and the beneficial effects if any of the antioxidant supplementation in cancer patients undergoing radiotherapy. Objectives: Since, antioxidants are known to detoxify Reactive oxygen species (ROS), the effect of antioxidant supplementation was studied in these patients. Methodology: Blood samples were drawn before and after the radiotherapy with or without antioxidant supplementation to estimate malondialdehyde (MDA) as an index of lipid peroxidation; the nitric oxide, Vitamin E and total antioxidant capacity (TAC) were estimated to assess the antioxidant status in these patients. Results: As compared to control, the MDAlevels were significantly increased while the levels of TAC, nitric oxide, Vitamin E were significantly reduced in these patients and more significantly in the patients after radiotherapy. While on supplementation with antioxidant therapy the levels of MDAwere significantly reduced and the levels of nitric oxide, Vitamin E and TAC were significantly elevated as compared to the group without antioxidant supplementation. Conclusion: Thus our findings confirm the presence of oxidative stress in cancer patients as well as the increase in oxidative stress by radiotherapy and suggest the possible preventive role of antioxidant supplementation in cancer patients undergoing radiotherapy.
Keywords: Antioxidant; Cancer; Radiotherapy; Oxidative stress; ROS